Two-axis beamsteering using a wideband Butler matrix and series-fed arrays for millimeter wave frequencies fabricated on metallic-nanowire-membrane platform - Simionato, Elígia [UNESP]; Aldaya, Ivan [UNESP]; Rosa, Guilherme S. [UNESP]; Lé, João E.G.; Serrano, Ariana L.C.; Rehder, Gustavo P.; Penchel, Rafael A. [UNESP] (Elsevier, 2024)
This work presents a two-axis beamsteering system designed for WLAN millimeter-wave frequencies. The system comprises a wideband Butler matrix and series-fed arrays. The Butler matrix, implemented with microstrip lines, features a wideband crossover with low phase imbalance, enabling four discrete beamsteering directions on the radiation H-plane. The series-fed arrays enable frequency-dependent beamsteering on the E-plane. The entire system was fabricated on a nanoporous alumina substrate using metallic-nanowire-membrane technology. Measurement results indicate an impedance bandwidth of 17.71%, which accommodates typical requirements for 60 GHz WLAN applications. Additionally, beamsteering in the desired directions was achieved. The presented Butler matrix structure stands out as one of the most compact found in the reviewed literature. The produced device successfully balances wideband behavior, compactness, and fabrication simplicity.
Keywords: Beamforming; Beamsteering; Butler matrix; Metallic-nanowire-membrane; Millimeter-waves; Series-fed array